Children On-Screen activity monitoring application - Lam, Chi Xiang (2022)

(untitled)
This project will be going to develop an interactive web application known as Children On-screen Activity Monitoring Application. Just like the name of the project, this is a parental monitoring application where it is specially designed to help parent to monitor their children on-screen activity during the online class in targeted devices. Since parenting children is not an easy job, hence the implementation of this system would provide a lot of conveniences to parent while saving time and cost instead of always keep an eye on their children. The limitation of this system is it only will start monitoring Children On-Screen Activity when they are attending their online class in the virtual platform such as Zoom and it will automatically stop monitoring after the children finish their class. Hence, the main purpose of this system is to help parent to monitor their children on-screen behavior during their online classes and the system also will protect the privacy of children once they finished their class. This is due to monitoring children’s activity for whole day could lead to children no longer believe on their parents and this will eventually affect the relationship between children and parents. Agile development approach will be used throughout the development of this project to deliver a quality system within time and budget. The reason for choosing this methodology because it is an iterative approach which able to minimize the risk associated with the development of the application. The target user of this system is child who will require to attend online classes during the Covid-19 pandemic. Database will also be implemented for the system to store the information of user and the information that extracted from the on-screen monitoring process and additional features such as keylogger and mouse tracker will be an advantage for this system to further keep track of children behaviour during the online class.